2007
DOI: 10.1007/s00268-007-9021-7
|View full text |Cite
|
Sign up to set email alerts
|

Stapled Transanal Rectal Resection (Starr) to Reverse the Anatomic Disorders of Pelvic Floor Dyssynergia

Abstract: Anterior rectocele and rectoanal intussusception are anatomic disorders related to excessive straining during defecation that usually manifest with symptoms of obstructive defecation. Stapled transanal rectal resection (STARR), a newly described surgical method for correcting these disorders, is considered a good alternative to the traditional transrectal approaches. The aim of the present study was to assess the early postoperative functional results of STARR. A total of 16 patients (13 female) were subjected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
56
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 27 publications
5
56
0
2
Order By: Relevance
“…22,[33][34] These conflicting observations are explained by the limited clinical use of STARR, as the literature accounts for fewer than 400 patients. These patients were recruited by different institutions that lack not only uniform inclusion/exclusion criteria but also expertise in stapler-assisted transanal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…22,[33][34] These conflicting observations are explained by the limited clinical use of STARR, as the literature accounts for fewer than 400 patients. These patients were recruited by different institutions that lack not only uniform inclusion/exclusion criteria but also expertise in stapler-assisted transanal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…When surgery is aimed at treating either enterocele or rectocele as an isolated lesion, it is unlikely to cure constipation, even when the anatomical disorder is corrected. 5,6,13,24 Occult rectal prolapse on straining is detected in 50 percent of normal subjects 25 but is present in 96 percent of patients with obstructed defecation. 1 However, constipation is relieved in just half of the cases when only prolapse excision is carried out.…”
Section: Discussionmentioning
confidence: 99%
“…In 2004, a study on STARR revealed that 90% of cases with ODS reported their overall satisfaction after STARR as good to excellent and only 4% of patients were described as poor [14]. In terms of efficacy, many studies showed an improvement of symptoms of obstruction after the procedure [12][13][14][15][16]. Results with STARR have been good.…”
Section: Discussionmentioning
confidence: 99%